Single K+ channel currents of anomalous rectification in cultured rat myotubes. - Ohmori, H (1981)
The currents through single K+ channels of the anomalous (or inward) rectifier were recorded in tissue cultured rat myotubes by using the "gigohm seal" patch clamp technique developed by Sigworth and Neher. These unitary currents were detected as current fluctuations due to the blocking and unblocking of channels by Ba2+. The single-channel conductance was obtained from the slope of the linear relationship between unitary current amplitude and membrane potential. When the external solution contained 155 mM K+, the single-channel conductance was 10.4 +/- 2.6 pS (+/- SD; n = 6). This value was independent of the the concentration of blocking ions but increased with increasing external K+ concentration. The behavior of the unitary current agreed with that expected from the blocking kinetics of Ba2+ on the macroscopic K+ current of the anomalous rectifier. The density of the channel is likely to be small and may even be less than 1/micrometers 2.